Identification of fungal clinical isolates by matrix-assisted laser desorption ionization-time-of-flight mass spectrometry. - Ferreira, Laura; Sánchez-Juanes, Fernando; Vega, Silvia; González, Magdalena; García, Ma Inmaculada; Rodríguez, Silvia; González-Buitrago, José Manuel; Muñoz-Bellido, Juan Luis (Revista Española de Quimioterapia, 2013)
Background. Recently, bacterial identification by MAL-DI-TOF MS has acquired a high relevance in terms of speed and reliability. Conventional mycological identification has some disadvantages: it is frequently slow, reliability is sometimes low, and an extensive experience is required. The risk popula¬tion for fungal infections, and therefore their clinical signifi¬cance has progressively increased in recent years. Methods. 153 yeast and mould clinical isolates were ana¬lyzed by MALDI-TOF MS and conventional identification. When both methods were discrepant to the genus or species level, ITS-2 sequencing was performed. Results. The correlation in yeasts identification between conventional identification methods and MALDI-TOF MS was extremely high (99.2% to the species level and 100% to the genus level). The only discrepancy was checked by ITS-2 se¬quencing and confirmed the MALDI-TOF identification. The correlation in moulds identification was more heterogeneous. 68.7% of the isolates showed correlation at least to the genus level and 40.6% to the species level. Therefore, the correlation between conventional identification and MALDI-TOF MS in fungal identification was, in whole, 87% to the species level, and 93.5% to the genus level. Conclusions. Identification of fungi by MALDI-TOF MS is reliable and shows potential advantages over conventional identification methods.